Sarcocystis atheridis sp. nov., a new sarcosporidian coccidium from Nitsche's bush viper, Atheris nitschei Tornier, 1902, from Uganda - Slapeta, J R; Modrý, D; Koudela, B (Parasitology research, 1999)
Transmission experiments were performed to elucidate the life cycle of a Sarcocystis sp. found in a Nitsche's bush viper, Atheris nitschei nitschei (Serpentes: Viperidae), from Uganda. Sporocysts measuring 10.4 (10.0-11.0) x 8.0 (7.0-8.5) microm were given to laboratory mice (Crl: CD1), laboratory rats (Wistar H), and Barbary striped mice, Lemniscomys barbarus. Sarcocysts developed in the skeletal muscles of laboratory mice and L. barbarus. No sarcocyst was observed in laboratory rats. Merogony was observed in the liver of L. barbarus at 7 and 12 days postinfection. Mature sarcocysts in mice reached a length of 30 mm and did not exceed 0.9 mm in diameter at 121 DPI. The primary sarcocyst wall was 0.6-0.8 microm thick and displayed small osmiophilic knob-like protrusions that were up to 150 nm long and 90 nm wide. Two types of asexual multiplication, endodyogony and endopolygony, were found within sarcocysts. Our results indicate that the newly found Sarcocystis represents a new species.
Keywords: myši inbrední ICR; myši; Viperidae; Mice, Inbred ICR; krysa rodu Rattus; Animals; Rats, Wistar; Mice; Sarcocystosis; Uganda; potkani Wistar; sarkocystóza; Sarcocystis; zvířata; Rats